How does the digital economy impact green manufacturing: A new perspective from the construction of a unified large market in China - Chenchen Wang; Yaobin Liu; Xuewen Liu; Haibo Xia (Humanities & Social Sciences Communications)
Abstract In the context of the global move into the digital economy (DEC) era and the accelerated development of the green industry, constructing a unified large market provides a powerful accelerating effect for the green transformation and upgrading of the manufacturing industry (GTUM) empowered by DEC. This study employs panel data combining China’s provincial level with the level of manufacturing subsectors from 2011 to 2020. It examines the impact of DEC and the construction of a unified large market on GTUM and its action mechanism at the theoretical and empirical levels by combining the traditional econometric models with geographic information systems, machine learning models, and other advanced technologies. Results indicate that DEC significantly enhances GTUM. Relative to the efficiency aspects of GTUM, the impact of DEC is more pronounced on energy consumption and environmental protection. Mechanism tests reveal that DEC primarily facilitates GTUM by reducing market segmentation effects, stimulating market potential effects, and matching market supply and demand effects. Heterogeneity analysis finds that in regions with higher levels of trade openness, technological innovation, and public environmental awareness, DEC more effectively promotes GTUM. Analyzing the temporal dynamics of this influence, the impact of DEC on GTUM aligns with Metcalfe’s Law, which posits a non-linear characteristic. Furthermore, the construction of a unified large market amplifies the effect of DEC empowering GTUM. This study offers a novel pathway for China to fully leverage DEC and the advantages of an ultra-large market to enhance the level of GTUM. It also provides valuable insights for the green development of industries globally.